FOOD EDUCATION ON SCHOOL CHILDREN'S SNACKS USING CREATIVE LEARNING MEDIA (E-BOOKLET) TO IMPROVE STUDENTS' KNOWLEDGE AT SMA NEGERI 5 PALU - Kiki Sanjaya; Pitriani Pitriani; Sendhy Krisnasari; Alchamdani Alchamdani; Adhe Sofyan Anas; Riri Suwahyuni Wahid; Ocvita Maharani; Adnan Sari Bite (Sean Institute, 2025)
School Children’s Snacks (PJAS) serve as one of the daily food sources for students; however, many issues regarding hygiene and food safety are still frequently found. The 2023 BPOM inspection revealed that 126 samples (55.75%) did not meet biological standards due to contamination by Escherichia coli. In addition, three samples of noodles and tofu (1.95%) were found not to meet chemical standards because they contained formalin. This situation is exacerbated by the lack of supervision from parents and teachers, as well as students’ limited knowledge about food safety. To address these problems, a community service program was conducted at SMA Negeri 5 Palu on August 25, 2025. The activity began with coordination between the principal and teachers regarding the use of an e-booklet as an educational medium for PJAS. A pre-test was carried out to assess students’ baseline knowledge, followed by counseling sessions delivered through short lectures, e-booklets, and videos. A post-test was then administered to measure knowledge improvement. To further motivate students, educational games with prizes were organized, and the PJAS e-booklet was handed over to the school for continuous use. Analysis of the pre- and post-test results showed a significant increase, both in understanding PJAS selection and awareness of harmful substances. Thus, this educational activity effectively enhanced students’ knowledge of safe PJAS consumption and helped reduce the risk of foodborne illness.